The Influence of Trust, Price and Lifestyle on Purchasing Decisions for Herbal Products in the New Normal Era with Buying Interest as an Intervening Variable - Sofiana, Evi; Elida, Sri Syabanita; Wahyuarini, Tri (Politeknik Negeri Bengkalis, 2024)
Currently, Indonesia is in a new normal era where Covid 19 cases can be suppressed. The economy that has not recovered due to the pandemic makes herbal products one of the choices for treating diseases. The number of herbal products in Indonesia makes consumers Â have many choices before deciding to buy this herbal product. The purpose of this study was to empirically examine the influence between trust, price, lifestyle and buying interest on the purchase decision of herbal products and to empirically examine the positive relationship between buying interest in mediating trust, price and lifestyle on purchasing decision herbal products in the new normal era. The research method used is a survey with questionnaires as a data collection tool. The sample was selected by the non-probability sampling method, namely convenience sampling. The distribution of questionnaires was carried out electronically to 130 respondents. Based on the results of the direct influence hypothesis test, it can be proven that there is a positive and significant influence of lifestyle on buying interest and purchasing decisions, with parameter coefficients of 0.698 and 0.510 and P-Values of 0.000. In addition, there is a positive and significant influence of buying interest on purchasing decisions with a parameter coefficient of 0.378 and P-Values of 0.000. But, trust and price didnâ€™t show significant influence to buying interest with parameter coefficients of 0.056 and 0.115 and P-Values of 0.543 and 0.169. In addition, trust and price also showed no significant influence on purchasing decisions with parameter coefficients of -0.027 and -0.005 and P-values of 0.720 and 0.962. For the indirect influence hypnosis test, lifestyle had a significant positive effect on purchasing decisions mediated by purchase interest with paremater coefficient values of 0.306, T-Statistic 3.845 and P-Value 0.000. while price and confidence showed no significant influence on purchasing decisions mediated by buying interest with paremater coefficient values of 0.066, and 0.022, T-Statistics 1.515 and 0.557 and P-Values 0.130 and 0.578.